2021
DOI: 10.1371/journal.pone.0249672
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 seroprevalence in military police force, Southern Brazil

Abstract: Background Limited data is available regarding the frequency of COVID-19 in populations that are highly exposed to SARS-CoV-2. In this cross-section study we evaluated COVID-19 seroprevalence in military police forces of 10 major cities in Rio Grande do Sul, South of Brazil. Methods Sampling was randomly performed in clusters, in respect to the number of professionals at service per city and military unit. Research subjects were evaluated on July 23, 2020 (first wave peak in Brazil). Clinical information was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…Opposite, the age range of the troops sets the personnel in a low-risk group to develop severe forms of the disease, explaining the lower fatality rate if compared to the one presented by the civil Colombian population. This was consistent with other military epidemiological surveillance studies conducted in countries of our region, such as Bolivia, Brazil, and the USA ( 13 15 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Opposite, the age range of the troops sets the personnel in a low-risk group to develop severe forms of the disease, explaining the lower fatality rate if compared to the one presented by the civil Colombian population. This was consistent with other military epidemiological surveillance studies conducted in countries of our region, such as Bolivia, Brazil, and the USA ( 13 15 ).…”
Section: Discussionsupporting
confidence: 93%
“…Although an exact attack rate of COVID-19 in the army health system could not be obtained, it, clearly, must be higher than the 8.55% reported for the confirmed cases ( 12 ). One must take into that active military personnel lives quartered in military forts or deploys in groups across the country, allowing rapid transmission of the virus in comparison with an incidence and prevalence of COVID-19 in studies with civil people ( 13 ). Opposite, the age range of the troops sets the personnel in a low-risk group to develop severe forms of the disease, explaining the lower fatality rate if compared to the one presented by the civil Colombian population.…”
Section: Discussionmentioning
confidence: 99%
“…14 , 15 Few seroprevalence studies focused on public safety personnel. 16 , 17 , 18 , 19 , 20 , 21 , 22 Garbarino et al 20 reported an overall seroprevalence of 4.8% in 10,535 police officers in Italy, with a higher seroprevalence in northern (9%) than in southern regions (1.6%).…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that these persons experience a potentially higher SARS-CoV-2 exposure risk due to the nature of their job than the general population [10,20,21]. Thus, according to the study of F-Y Lan et al (2020), employees with direct customer exposure were five times more likely to test positive for SARS-CoV-2 [18], while the seroprevalence of COVID-19 amongst police officers was at least 3.4 higher than in the general population [36]. Nevertheless, some recent data suggest that the seroprevalence of SARS-CoV-2 antibodies in persons from high-risk groups is similar [3] or only marginally higher [10,37] compared to that in the general population, depending on regional variation in COVID-19 incidence.…”
Section: Discussionmentioning
confidence: 99%